Three-year changes of prothrombotic factors in a cohort of South Africans with a high clinical suspicion of obstructive sleep apnea - Känel, Roland von; Malan, Nico T.; Hamer, Mark; Lambert, Gavin W.; Schlaich, Markus; Reimann, Manja; Malan, Leoné (Thrombosis and Haemostasis, 2016)
A hypercoagulable state might be one important mechanism linking obstructive sleep apnea (OSA) with incident myocardial infarction and stroke. However, previous studies on prothrombotic factors in OSA are not uniform and cross-sectional. We longitudinally studied prothrombotic factors in relation to OSA risk, adjusting for baseline levels of prothrombotic factors, demographics, metabolic parameters, aspirin use, and life style factors. The Berlin Questionnaire and/or neck circumference were used to define high OSA risk in 329 South African teachers (48.0 % male, 44.6 % black) at baseline and at three-year follow-up. Von Willebrand factor (VWF), fibrinogen, D-dimer, plasminogen activator inhibitor-1, clot lysis time (CLT), and soluble urokinase-type plasminogen activator receptor (suPAR) were measured in plasma. At baseline 35.7 % of participants had a high risk of OSA. At follow-up, persistently high OSA risk, persistently low OSA risk, OSA risk remission, and new-onset OSA risk were present in 26.1 %, 53.2 %, 9.4 %, and 11.3 % of participants, respectively. New-onset OSA risk was associated with a significant and longitudinal increase in VWF, fibrinogen, CLT, and suPAR relative to persistently low OSA risk; in VWF, fibrinogen, and suPAR relative to remitted OSA risk; and in VWF relative to persistently high OSA risk. Persistently high OSA risk was associated with an increase in CLT and suPAR relative to persistently low OSA risk and in D-dimer relative to remitted OSA risk. Remitted OSA risk was associated with D-dimer decrease relative to persistently low OSA risk. In OSA, hypercoagulability is a dynamic process with a most prominent three-year increase in individuals with new-onset OSA risk.
Keywords: Blood coagulation; cardiovascular disease; fibrinolysis; longitudinal study; risk factor; sleep disordered breathing